2008
DOI: 10.1007/s10646-008-0233-x
|View full text |Cite
|
Sign up to set email alerts
|

Sediment copper bioavailability to freshwater snails in south Florida: risk implications for the Everglade snail kite (Rostrhamus sociabilis plumbeus)

Abstract: Many properties being acquired as part of the Comprehensive Everglades Restoration Plan (CERP) are heavily contaminated with copper. Estimated copper bioaccumulation in the Florida apple snail (Pomacea paludosa) has led to the prediction of risk to the Everglade snail kite (Rostrhamus sociabilis plumbeus) at some CERP projects. Field study results presented in this paper examine the relationship between copper levels in sediments, snails, and other biota. Copper concentrations in all biota (snails, aquatic vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, by directly spraying those metals to the field or soil initiates the environmental contamination. Cu‐contaminated environment in soil, sediment and overlying water, as a result of Cu exposures to the pest snails, is a major concern . To avoid dramatically environmental problem by direct applying, a production of the Cu‐based pesticide film would serve as a practical way for controlling pest snail and reducing the environmental impact.…”
Section: Introductionmentioning
confidence: 99%
“…However, by directly spraying those metals to the field or soil initiates the environmental contamination. Cu‐contaminated environment in soil, sediment and overlying water, as a result of Cu exposures to the pest snails, is a major concern . To avoid dramatically environmental problem by direct applying, a production of the Cu‐based pesticide film would serve as a practical way for controlling pest snail and reducing the environmental impact.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have evaluated the possibility of using apple snails as sentinels of elemental pollution in freshwater bodies (Adewunmi et al, 1996;Deng et al, 2008;Ezemonye et al, 2006;Frakes et al, 2008;Hoang et al, 2008;Maltez et al, 2009;Vega et al, 2012a) the influences of chemical, biological and temporal factors on the elemental partitioning are not fully understood. The central objective of the current work was to shed light on the role of the kidney, digestive gland and its intracellular symbiotic corpuscles of P. canaliculata in the bioconcentration and depuration processes of three elements: mercury (class B), arsenic (intermediate class) and uranium (class A).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of copper exposure on the F 0 generation of ASs did not seem to affect the survival, growth, or whole-body copper concentration of the subsequent F 1 generation [77]. Recent studies have revealed that copper accumulation in ASs (P. paludosa) can pose a significant risk to predators of Florida apple snails, such as the snail kite (Rostrhamus sociabilis plumbeus) [78][79][80][81]. In addition, ASs (P. canaliculata) showed significant pathological alterations in tissues in copper-rich environments, suggesting that ASs can serve as a biomonitor of copper contamination in freshwater environments [82,83].…”
Section: Hotspot Research For Abstract Clustermentioning
confidence: 99%